Evaluasi Sistem Informasi Manajemen Rumah Sakit Di Instalasi Rekam Medis RSUP H. Adam Malik Dengan Metode Human Organization Technology Fit (HOT-FIT) Tahun 2019 - Welly Satria Dewi; Daniel Ginting; Rumondang Gultom (Jurnal Ilmiah Perekam dan Informasi Kesehatan Imelda, 2021)
Based on the regulations of the Act – Act number 44-year 2009 about hospitals, where each hospital is obligated to do the recording and reporting of all activities of the Organization of the hospital in the form of hospital management information system (SIMRS). Therefore, every hospital is obligated to run SIMRS with the use of open source as has been set in the Year 2013 No. 82 Permenkes about SIMRS. The purpose of the study in order to evaluate the management information system in hospital medical record Installation was RSUP. Adam Malik. Quantitative research method withcross sectional design to measure the research variables model HOT Fit: Human (the use of the system, user satisfaction), Technology (quality system, the quality of information and service quality), Organization (structure), against a Net benefit. Population is the entire staff of medical record that uses SIMRS of 69 people, sampling techniques are the total sampling. The data analysis done in a multiple regression. The purpose of the study to find out the influence of the factor of human technology is preferred, and the organization 's response to the net benefit. The results of the research there is the influence of human factors and technology against a net benefit to mean Ho denied and Ha was accepted, while to factor the organization has no influence on the net benefit, meaning that Ho and Ha accepted rejected. Simultaneously all the independent variables have significant effects on the dependent variable i.e. factors human, technology and organization, the impact on the net benefit. The R-squared value of 0.635 which means all variables the dependent variable may affect independent of 63.5%. Conclusion the research need to craft a careful planning for the development of SIMRS in order to get a quality system, quality of information and service quality, and poured in the master plan, and strategic plan of the hospital.